The Role of Postal Networks in Expanding Access to Financial Services : Kazakhstan's Postal Finance Services - World Bank (Washington, DC, 2013)
This paper discusses the role of the postal network in expanding access to financial services in Kazakhstan. It reviews the public postal operator within the postal sector and within the broader context of the communications sector. The roles of the postal network and state and privately-owned banks are also reviewed from the perspective of the financial sector development, with particular focus on payments systems development and microfinance. While this country case on Kazakhstan can stand alone, it is an integral part of this large study of the potential of postal networks to coordinate with financial service providers in 7 countries (Egypt, Kazakhstan, Namibia, Romania, Sri Lanka, Uganda, and Vietnam) and 5 regions (Africa, Asia, Eastern Europe and Central Asia, Latin America and the Caribbean, and the Middle East and Northern Africa). Within Central Asia and the other countries of the former Soviet Union, Kazakhstan's postal network is widely regarded as a leader and pioneer in postal innovation, setting an example for other postal operators in the region. An in-depth assessment of Kazakhstan's postal network development options could also be a model to guide other postal networks.